Analysis and characterization of the hyperchaos generated by a semiconductor laser subject to a delayed feedback loop - Vicente, R.; Dauden, J.; Colet, P.; Toral, R. (IEEE journal of quantum electronics, 2005)
We characterize the chaotic dynamics of semiconductor lasers subject to either optical or electrooptical feedback modeled by Lang-Kobayashi and Ikeda equations, respectively. This characterization is relevant for secure optical communications based on chaos encryption. In particular, for each system we compute as a function of tunable parameters the Lyapunov spectrum, Kaplan-Yorke dimension and Kolmogorov-Sinai entropy.